Detection of asymptomatic recurrence following curative surgery improves survival in patients with gastric cancer: A systematic review and meta-analysis - Pang, Hua-Yang; Yan, Meng-Hua; Chen, Li-Hui; Chen, Xiu-Feng; Chen, Zhi-Xiong; Zhang, Shou-Ru; Sun, Hao (Frontiers in Oncology, 2022)
Background To date, there is no evidence that intensive follow-up provides survival benefit in gastric cancer patients undergoing curative gastrectomy. The aim of this study is to investigate the efficacy of detection of asymptomatic recurrence using intensive surveillance strategy in long-term survival after curative gastric cancer surgery. Methods A systematic review of electronic databases including PubMed, Embase, Web of Science, the Cochrane Library and China National Knowledge Infrastructure, Clinical Trials Registry and Google Scholar was performed up to April 2022. The primary outcomes were survival outcomes: overall survival, recurrence-free survival and post-recurrence survival. The secondary endpoints were clinicopathological features, recurrence patterns and treatment after recurrence. The registration number of this protocol is PROSPERO CRD42022327370. Results A total of 11 studies including 1898 participants were included. In the pooled analysis, the detection of asymptomatic recurrence was significantly associated with an improved overall survival compared to patients showing symptoms of recurrence (HR=0.67; 95%CI: 0.57-0.79; P<0.001), which was primarily driven by the prolongation of post-recurrence survival (HR=0.51; 95%CI: 0.42-0.61; P<0.001), since there was no significant difference observed in recurrence-free survival (HR=1.12; 95%CI: 0.81-1.55; P=0.48) between the two groups. Meanwhile, male sex and advanced T stage were more frequently observed in the symptomatic recurrence group. Furthermore, patients in the symptomatic recurrence group had a higher proportion of peritoneal relapse but lower proportion of distant lymph node metastasis. Additionally, patients in the symptomatic recurrence group were less likely to receive surgery treatment and post-recurrence chemotherapy. Conclusion The detection of asymptomatic recurrence using intensive follow-up was associated with an appreciable improvement in overall survival. However, more robust data from high-quality studies are still required to verify this issue. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=327370, identifier CRD42022327370.